Dampak adopsi artificial intelligence pada produktivitas umkm di indonesia - Jailani, Mohammad Shohibul Fajar (Maliki Interdisciplinary Journal, 2026)
The development of Artificial Intelligence (AI) brings significant transformation opportunities for the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia. This study aims to analyze the impact of AI adoption on increasing the productivity of MSMEs through operational efficiency, digital marketing optimization, and strengthening data-based decision-making. The research method is carried out through literature studies from relevant national and international journals. The results show that AI contributes positively to accelerating workflows, improving the accuracy of market analysis, and expanding the reach of marketing through automation and personalization of services. However, the adoption of AI by MSMEs still faces obstacles in the form of limited digital literacy, implementation costs, and lack of supporting infrastructure. This research emphasizes the need for multi-stakeholder collaboration to strengthen an inclusive and affordable technology adoption ecosystem for MSMEs in Indonesia.